Information Asymmetry as an Intervening Variable on the Effect of Earnings Quality on the Cost of Equity - I Gde Andhika Putra; M. Ali Fikri; Iman Waskito; Ermawati, Ermawati; Augustine Ayuba (Tinta Emas Publisher, 2023)
The increasing competition demands companies to expand their operations in order to survive and remain competitive. This expansion includes business expansion, product innovation, and product differentiation, all of which ultimately lead to an increased need for funding. Therefore, companies require external parties capable of providing funding, such as investors or creditors. The objective of this research is to examine whether the quality of earnings affects the cost of equity and whether the quality of earnings affects the cost of equity with asymmetric information as an intervening variable. The quality of earnings is measured using discretionary accruals, which are calculated using the Modified Jones Model. Meanwhile, asymmetric information and the cost of equity are measured using bid-ask spreads and price-earning ratios, with agency theory as the primary theory underpinning this research. The research sample consists of 46 companies selected through purposive sampling from the manufacturing sector of consumer goods industry listed on the Indonesia Stock Exchange during the years 2019-2021. The research method employed in this study is path analysis, which explains the direct and indirect relationships between the quality of earnings, asymmetric information, and the cost of equity. Based on the results of the path analysis, it is evident that the quality of earnings does not directly affect the cost of equity. Furthermore, the testing of the second hypothesis indicates that the quality of earnings does not have an indirect effect on the cost of equity with asymmetric information as an intervening variable.